The influence of innovation on the competitiveness of frozen food MSMEs in Medan City - Faiz Ahmad Sibuea; Muhammad Buhari Sibuea; Apip Gunaldi Dalimunthe (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
The competitiveness of frozen food Micro, Small, and Medium Enterprises (MSMEs) in Medan City is increasingly important in the context of a rapidly growing economy, especially in facing significant challenges such as intense competition. Innovation is a crucial factor in creating competitive advantage and expanding the market for frozen food MSMEs. This study analyzes the level of innovation and competitiveness of frozen food MSMEs and the influence of innovation on the competitiveness of frozen food MSMEs in Medan City. The sample of this study was all frozen food MSMEs under the guidance of the Medan City Cooperatives and SMEs Office, totaling 50 actors. This study is qualitative using a Likert scale to measure innovation and competitiveness of frozen food MSMEs, while SEM-PLS is used to analyze the influence of innovation on competitiveness. The results show that the level of innovation of frozen food MSMEs is in the good category with a score of 185.16 (74.06%). Meanwhile, the competitiveness of frozen food MSMEs is also in the good category with a score of 193 (77.2%). Furthermore, the results of SEM-PLS processing show that there is an influence of MSME actors' innovation on the competitiveness of frozen food MSMEs in Medan City, which is indicated by a P-value of less than 0.05.